2019
DOI: 10.1111/petr.13380
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication use trends in a large pediatric and young adult solid organ transplant population

Abstract: Introduction This study describes psychotropic medication use in a pediatric and young adult solid organ transplant population. Methods We conducted a retrospective review of the lifetime incidence of psychotropic medication use and associated characteristics in patients seen over a 6‐year period at a large pediatric transplant center utilizing univariate and multivariate statistical analyses. Results The lifetime incidence of psychotropic medication use was 36.5% in 393 patients. Transplant psychiatry provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It is also possible that antidepressant medications may have been prescribed as part of palliative care, given increasing involvement of psychiatry during end-of-life care. 105 The low rate of antidepressant medication use in this British study (<5%) highlights the difference in prescribing patterns between countries. In a similar study from the United States, the rate of documented antidepressant use in adults with congenital heart disease was 18%.…”
Section: Mental Health Interventionsmentioning
confidence: 66%
“…It is also possible that antidepressant medications may have been prescribed as part of palliative care, given increasing involvement of psychiatry during end-of-life care. 105 The low rate of antidepressant medication use in this British study (<5%) highlights the difference in prescribing patterns between countries. In a similar study from the United States, the rate of documented antidepressant use in adults with congenital heart disease was 18%.…”
Section: Mental Health Interventionsmentioning
confidence: 66%
“…A significant question remains if depression improves after transplantation. Several authors reported that depression improved posttransplant or was less common posttransplant compared with pretransplant in heart and kidney recipients [23,27,40,46,50]. In liver recipients, however, two studies found that depression worsens after transplantation [43,51].…”
Section: Key Pointsmentioning
confidence: 99%
“…Antidepressant use in the first year after kidney transplant was associated with two-fold higher risk of death, 38% higher risk of death-censored graft failure and 61% higher risk of all-cause graft failure in the subsequent year [26]. This is especially concerning considering that the lifetime prevalence of antidepressant use in transplant patients is significant (15% [27]).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health issues are also more common in pediatric organ transplant recipients, which can impact cognitive, school, and social functioning. In one single‐center study, over 30% of pediatric and young adult transplant recipients were found to receive psychotropic medications over their lifetimes, illustrating the need for psychiatric involvement in the management of many of these patients 28 …”
Section: Transition Back To Schoolmentioning
confidence: 99%
“…In one single-center study, over 30% of pediatric and young adult transplant recipients were found to receive psychotropic medications over their lifetimes, illustrating the need for psychiatric involvement in the management of many of these patients. 28 The families, primary care physicians, and schools of pediatric transplant recipients need to be educated about these potential risks, so that they are screened for and addressed with early intervention if needed. Although the utility may differ based on type of organ transplant and specific patient characteristics, some have suggested that formal neuropsychological assessment be included as part of standard post-transplant care (Table 1).…”
Section: Cognitive Concernsmentioning
confidence: 99%